Preconditions for the Tax Environment of a Alterglobal Development - Krysovatyy, Andriy I.; Zvarych, Iryna Ya.; Zvarych, Roman Ye.; Zhyvko, Maksym An. (Comparative Economic Research. Central and Eastern Europe, 2018)
In this article, we analyzed economic surroundings as a precondition for the development of the tax environment in the context of alterglobal development. We admitted that economic globalization is harmful to the environment because it depends on its own viability: the constant increase in commodity consumption, the increased use of resources and the growing disposition to pollute waste in the ocean, on the ground, and in the air. So, we proposed considering and analyzing alterglobalization as a process oriented towards self‑determination for peoples, communities and nations. In this context, we developed the idea about Environmental Fiscal Reform, including increasing green taxation and the phase‑out of environmentally harmful subsidies as well as financial incentives, VAT reductions and tax breaks for green initiatives – providing the perfect conditions for the transition to a circular economy. As the new economy is developing at a rapid pace today – 10% per year, more than three times the global economic growth rate – it has a significant impact on competitiveness.